Doping w sporcie jako problem etyczno-społeczny = Doping in sport as a problem ethical and social - Aleksandra Lewandowska (Journal of Education, Health and Sport, 2016)
Lewandowska Aleksandra, Leźnicki Marcin. Doping w sporcie jako problem etyczno-społeczny = Doping in sport as a problem ethical and social. Journal of Education, Health and Sport. 2016;6(7):548-555. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59006